STUDY ON CONTRACEPTIVE USE AND FAMILY PLANNING WITH HAITIAN IMMIGRANTS - Allebrandt, Bruna Letícia; Dambrós, Bibiana Paula; Winck, Daniela (Anuário Pesquisa e Extensão Unoesc Videira, 2017)
Introduction: The main activity of family planning is to provide couples with information to enable them to decide the number of children they want and when they want, consciously and voluntarily. In Brazil, the State is responsible for providing educational and financial resources regarding family planning, but the arrival of Haitian immigrants raises the curiosity about the way these women develop family planning. Objective: to assess the use of contraceptive methods and the knowledge on family planning of Haitian immigrants. Materials and Methods: Exploratory study with a quantitative approach using a research instrument with variables related to contraceptive methods and knowledge of family planning. Sixteen Haitian women, workers of a company in Videira, Santa Catarina, were interviewed. Results: the age of the interviewees ranged between 19 and 49 years; 37.5% were single and 62.5% were married. Most of the interviewees (68.5%) were not aware of contraceptive methods in Haiti, and 25% only became aware of these methods after coming to Brazil. The vast majority (81.25%) reported to have children, with an average of 1.56 per women; 56.25% had left their children in Haiti in order to immigrate. Besides, 18.75% reported miscarriages/abortions. Regarding family, 93.75% reported that families are culturally large in Haiti; 68.75% were not aware of family planning. Conclusion: The study evidences that Haitian immigrants have no adequate information about contraceptive methods, prevention of unwanted pregnancies, and abortions. Keywords: Contraceptive methods. Family planning. Haitian immigrants.